Milestones of dental history - Rajesh Mahant; S Vineet Agrawal; Sonali Kapoor; Isha Agrawal (Wolters Kluwer Medknow Publications, 2017)
Since ages, human beings suffer from the dental problems. With the journey as time elapsed the person treating the teeth changed (i.e., from barbers and monks to present dentists), equipment changed (i.e., from bow drills to airotor and laser handpieces), materials changed (i.e., from ground mastic alum/honey to tooth colored composite and ceramics). There has been drastic change in treatment planning from extraction to the conservation of teeth and from manual restoration to computerized restorations computer-aided design/computer-aided manufacturing. Thus, this review is an attempt to have an insight into major milestones of the dental timeline.